THE INFLUENCE OF BUSINESS CAPITAL, BUSINESS COMPETITION ON THE DEVELOPMENT OF MOBILE PHONE SMES IN MEDAN - Anni Wati Tumanggor; Rindi Andika; Via Vio Ninda; Intan Amandayu; Muhammad Fakhri Lubis (Universitas Efarina, 2022)
The object of this research on Amy Mobile phone located in Area Jendral Gatot Subroto Medan is one of the businesses engaged in the sale of various brands of mobile phones and at the same time repair damage all kinds of brand mobile phones. Problems in this study related to business capital and market competition on the development of Small Micro Business Cellular Phone Amy Mobile in Medan. The result of the research shows that business capital, Market Competition simultaneously and significantly influence to Micro Small Business development, while partially positive and significant business capital variable influence to micro small business development and market competition variables have positive and significant influence on Micro Small Business development. Determination of the results of this study shows the development of Micro Small Business bias is explained by independent variables of business capital and market competition, while the rest (100% -85.1% = 14.9%) can be explained by other variables that have not been meticulously.